Executive Privilege : Presidential Power, Secrecy, and Accountability - Rozell, Mark J. (Book collections on Project MUSE., 2020)
"Mark Rozell's Executive Privilege-called "the definitive contemporary work on the subject" by the Journal of Politics-is widely considered the best in-depth history and analysis of executive privilege and its relation to the proper scope and limits of presidential power. Picking up where the third edition left off-with President Barack Obama's claim to begin a new era of transparency-this revised and updated fourth edition, with assistance from Mitchel Sollenberger, provides a thorough analysis of the controversies from the past decade, including Obama's failure to live up to the high expectations of his campaign promises and President Donald Trump's bold assertion of a "protective executive privilege" that recognizes no balancing powers against the executive branch. The new edition covers the investigations into three controversies of the Trump presidency: the Russian meddling in the 2016 elections, the proposed addition of a citizenship question on the 2020 Census, and the ongoing inquiry into White House security clearances"--